Technical complexity and consumer knowledge as moderators of service quality evaluation in the automobile service industry - Andaleeb, Syed Saad; Basu, Amiya K. (© 1994 New York University., 2016)
This article was published in the Journal of Retailing [© 1994 New York University] and the definite version is available at : http://doi.org/10.1016/0022-4359(94)90005-1 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/0022435994900051